2009
DOI: 10.1186/1749-8546-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Minimal acupuncture is not a valid placebo control in randomised controlled trials of acupuncture: a physiologist's perspective

Abstract: Placebo-control of acupuncture is used to evaluate and distinguish between the specific effects and the non-specific ones. During 'true' acupuncture treatment in general, the needles are inserted into acupoints and stimulated until deqi is evoked. In contrast, during placebo acupuncture, the needles are inserted into non-acupoints and/or superficially (so-called minimal acupuncture). A sham acupuncture needle with a blunt tip may be used in placebo acupuncture. Both minimal acupuncture and the placebo acupunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
144
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(152 citation statements)
references
References 94 publications
(71 reference statements)
0
144
0
8
Order By: Relevance
“…Indeed, a recent meta-analysis found that SA was much more effective than sham oral pharmaceutical placebos for migraine prophylaxis (4). Although the response to SA has led skeptics to consider the acupuncture effect no more than placebo, it remains quite possible that the sham interventions being studied are non-inert or acting via a different mechanism (5). Further evaluation of the contribution of the placebo effect to acupuncture is essential to addressing these methodological challenges about efficacy and to advancing the science of the field.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent meta-analysis found that SA was much more effective than sham oral pharmaceutical placebos for migraine prophylaxis (4). Although the response to SA has led skeptics to consider the acupuncture effect no more than placebo, it remains quite possible that the sham interventions being studied are non-inert or acting via a different mechanism (5). Further evaluation of the contribution of the placebo effect to acupuncture is essential to addressing these methodological challenges about efficacy and to advancing the science of the field.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is debatable whether the clinical effects of acupuncture are restricted to stimulation on points that lie on the classical meridians in TCM. Our finding that laser stimulation of a non-acupoint produced some brain activation suggest that there is unlikely to be a completely neutral control non-acupoint, and this should prompt a re-examination of the use of sham points (in needle acupuncture studies) as control hence minimizing the true statistical effects of any acupoint [36][37][38][39]. It is also interesting that laser acupuncture in this study appeared to preferentially activate the limbic cortex ipsilaterally and deactivate the limbic cortex contralaterally.…”
Section: Discussionmentioning
confidence: 85%
“…Doubts about whether minimal or nonpoint-specific acupuncture conditions are really physiologically inactive for the treatment of pain have been raised. 59,60,[66][67][68] If so, then a comparison of two active treatments is very likely to show no group difference and the conclusion that the investigated treatment is ineffective would be misleading. However, a recent individual meta-analysis based on data from 29 randomized clinical trials with a total of 17,922 patients reported clear differences between real acupuncture and sham procedures for several chronic pain conditions.…”
Section: Discussionmentioning
confidence: 99%